The Need to Implement Internal Control and The Applicability of Internal Control Standards - Rareș-Cosmin NICORICI (Communications of International Proceedings, 2022)
The internal control management system is like a living organism and must update its form frequently, thus managing to remain effective for the institution being implemented and improved by each employee and not left only on the shoulders of the board of directors or the management departments in each section / structure. The Code of Internal Management Control of public entities has as a starting point the control models implemented both at European and international level. The good faith shown by Romania, regarding the implementation of a control taking into account the particularities in the country, opted for the elaboration and adoption of its own internal control system and not by applying an international internal control system. The implementation of internal control is not an easy task for the monitoring committee, nor for the person designated with the monitoring, and all this is difficult to achieve due to the bureaucratic system in public entities, resistance to change, insufficient support from management, insufficient training and lack of practical examples.
Keywords: Internal Control; Internal Control Standards; SCIM